2020
DOI: 10.1093/molbev/msaa325
|View full text |Cite
|
Sign up to set email alerts
|

Like Wings of a Bird: Functional Divergence and Complementarity between HLA-A and HLA-B Molecules

Abstract: Human leukocyte antigen (HLA) genes are among the most polymorphic of our genome, as a likely consequence of balancing selection related to their central role in adaptive immunity. HLA-A and HLA-B genes were recently suggested to evolve through a model of joint divergent asymmetric selection conferring all populations, including those with severe loss of diversity, an equivalent immune potential. However, the mechanisms by which these two genes might undergo joint evolution while displaying very distinct allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…The median promiscuity level was significantly higher for variants of the HLA-A locus compared with HLA-B and HLA-C loci. Multiple studies on distinct properties of HLA class-I variants revealed differences among these loci, especially between HLA-A and HLA-B loci ( Di et al 2021 ). Prugnolle et al (2005) reported that the positive correlation between pathogen richness and allelic diversity is much stronger for the HLA-B locus than the HLA-A locus.…”
Section: Discussionmentioning
confidence: 99%
“…The median promiscuity level was significantly higher for variants of the HLA-A locus compared with HLA-B and HLA-C loci. Multiple studies on distinct properties of HLA class-I variants revealed differences among these loci, especially between HLA-A and HLA-B loci ( Di et al 2021 ). Prugnolle et al (2005) reported that the positive correlation between pathogen richness and allelic diversity is much stronger for the HLA-B locus than the HLA-A locus.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of the HLA molecules’ evolution have interpreted HLA diversity differently. Kaufman et al ( Kaufman, 2018 ; Di et al, 2021 ) have proposed promiscuous and generalist HLA categories when Di et al have challenged the concepts of supertypes and function peptide-binding groove groups.…”
Section: Generating and Working With Hla Datamentioning
confidence: 99%
“…In this context, we designed a procedure of assignment to adapt the 1st-field genotype data to 2nd-field prediction results, using high-resolution HLA data from a Yazd Iranian population as reference. As for HLA-C , the gene was previously suggested to be much less expressed and display less unique peptide repertoire compared to HLA-A and -B ( 34 , 63 ), and the latter was again confirmed by the overall number of binders to HLA-A, -B, and -C molecules (n ABC ; Figures 4 , Supplementary Figures 7 – 9 ). Nevertheless, synthetic analyses including high-resolution HLA Class I case–control data from different populations will be necessary.…”
Section: Discussionmentioning
confidence: 62%
“…The list of our 2nd-field HLA alleles includes all those considered as “commonly” distributed in worldwide population (observed in at least five populations) that we defined in a previous study ( 34 ). In order to adapt the prediction results for 2nd-field alleles to our 1st-field data of patients and controls, we assigned each observed 1st-field allele to the most probable 2nd-field one, using as a reference a set of 2nd-field HLA-A , -B , and -DRB1 allele frequency data recently reported for 90 Iranians from Yazd province in the center of Iran ( 35 ), who share similar ethno-linguistic background with Hamadan people ( Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%